HARNESSING THE MULTI-DIMENSIONAL BENEFITS OF RIVER NIGER THROUGH TRANS-NATIONAL INTEGRATION - (Ph.D), OBI LAWRENCE E (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
The research worked on how transnational integration of the riparian nations of the River Nigercan be used to harness fully the multi-dimensional potentialities of the river. The paper addressedthe role of the Niger Basin Authority in achieving the trans-national integration and came upwith methods of harnessing the multifarious benefits derivable from the approach of transnationalintegration. From the opinion of the paper the multi-dimensional benefits includedsustainable water development, harmonized hydroelectric power, improved agriculturalproductivity, enhanced water transportation, adequate water supply, arbitration of boundaryconflicts and tourism